Antecedent of Job Stress: Causes Need to be Identified A Case of Secondary School Teachers - SHAHZAD KHAN; Dr. MUHAMMAD TARIQ KHAN; MUHAMMAD ATIQ RAFIQUE KHATTAK (Journal of Business & Tourism, 2021)
The purpose of the study is to identify the possible antecedents of stress in secondary schools teaches. Many factors are there which lead stress specifically in private sectors. However it’s important to find the essential role playing factor of stress in private schools teachers. The research identified the antecedents of job stress in private schools teachers in Peshawar Pakistan. Population of the study has been chosen on convenience sampling a non-probability technique. A 5 point lickert Scale structured questionnaire was distributed among 100 schools teachers. The data collected through questionnaires was analyzed and interpreted using ANOVA, and Regression co-efficient. The findings of the study revealed that co-worker relation and school discipline are the key factors of schools teachers stress.